A 27-MHz frequency shift keying wireless system resilient to in-band interference for wireless sensing applications - Thannatorn Boonrungruedee; Phanumas Khumsat (Institute of Advanced Engineering and Science, 2023)
A 27-MHz wireless system with binary frequency shift keying (BFSK) modulation at 400-kHz is reported. The receiver has been designed to handle in-band interference corrupting the BFSK signal with the use of complex filters and amplitude comparison method. The BFSK modulation is carried out with a voltage-controlled oscillator before up-converting with a 27-MHz local oscillator. The bipolar junction transistors (BJT-based) power amplifier with 30% efficiency pumps 220 mW into a spiral antenna. The inductive-degenerated low-noise amplifier with a voltage of more than 30 dB amplifies an incoming signal before feeding into a mixer for complex direct down conversion. With deliberate Gaussian interference injection, the minimum ratios between the signal with interference and the interference only at the distance of 2.5, 10 and 15 m are 3.3, 8.5 and 11.5 dB, respectively at a maximum data rate of 20 kbps. Without any interference included, the system can achieve a data rate of 40 kbps at the maximum transmission distance of 15 m. Conceptually agreed with the presented bit-error-rate (BER) analysis, the BER measurements with Gaussian and single-tone/two-tone in-band interferences also confirm superiority offered by the amplitude comparison method where the signal-to-noise ratio is at 1 dB for BER=10-3 at 10 kbps (10 dB better than the phase detection counterpart).